Database Mining to Unravel the Ecology of the Phylum Chloroflexi in Methanogenic Full Scale Bioreactors - Bovio-Winkler, Patricia; Cabezas, Angela; Etchebehere, Claudia (Frontiers in Microbiology, 2021)
Although microbial communities of anaerobic bioreactors have been extensively studied using DNA-based tools, there are still several knowledge gaps regarding the microbiology of the process, in particular integration of all generated data is still limited. One understudied core phyla within anaerobic bioreactors is the phylum Chloroflexi, despite being one of the most abundant groups in anaerobic reactors. In order to address the abundance, diversity and phylogeny of this group in full-scale methanogenic reactors globally distributed, a compilation of 16S ribosomal RNA gene sequence data from 62 full-scale methanogenic reactors studied worldwide, fed either with wastewater (WTARs) or solid waste (STARs), was performed. One of the barriers to overcome was comparing data generated using different primer sets and different sequencing platforms. The sequence analysis revealed that the average abundance of Chloroflexi in WTARs was higher than in STARs. Four genera belonging to the Anaerolineae class dominated both WTARs and STARs but the core populations were different. According to the phylogenetic analysis, most of the sequences formed clusters with no cultured representatives. The Anaerolineae class was more abundant in reactors with granular biomass than in reactors with disperse biomass supporting the hypothesis that Anaerolineae play an important role in granule formation and structure due to their filamentous morphology. Cross-study comparisons can be fruitfully used to understand the complexity of the anaerobic digestion process. However, more efforts are needed to standardize protocols and report metadata information.